Open source for knowledge and learning management strategies beyond tools - Lytras, Miltiadis D. 1973-; Naeve, Ambjorn (Idea Group Pub., 2007)
"This book presents learning and knowledge management from a point of view where the basic tools and applications are provided by open source technologies, It explains an intese orientation to the critical issues of the open source paradigm: open source tools, applications, social networks, and knowledge sharing in open source communities"--Provided by publisher